PENEGAKAN HUKUM TERHADAP KEGIATAN PERTAMBANGAN BATUBARA TANPA IZIN DI KAWASAN TAMAN HUTAN RAYA BUKIT SOEHARTO - Mazaya Aliya Jovilina; Mis Joni (Law Department, University of Widya Gama Mahakam Samarinda, 2025)
Background: Bukit Soeharto Grand Forest Park is a conservation area of ​​64,814.98 ha with rich and diverse natural resource potential so that it requires licensing for business activities that are considered to be able to damage and/or pollute the forest area, but in this area there are coal mining activities without a permit so that they damage and pollute the Bukit Soeharto Grand Forest Park area. This study aims to examine and analyze law enforcement efforts against coal mining activities without a permit in the Bukit Soeharto Grand Forest Park area and examine the inhibiting factors in law enforcement efforts against coal mining activities without a permit in the Bukit Soeharto Grand Forest Park area. Research Metodes: In this research, the author uses a socio-legal research.. Findings: Law enforcement efforts against illegal coal mining activities in the Bukit Soeharto Grand Forest Park area are carried out by the Balai Gakkum LHK Kalimantan as a Civil Servant Investigator and also the UPTD Tahura Bukit Soeharto as a Regional Technical Implementation Unit. The UPTD Tahura Bukit Soeharto in its law enforcement efforts (1) Receives reports from the public, (2) Manages and supervises the Tahura Bukit Soeharto area by conducting patrols in the Bukit Soeharto Grand Forest Park area, and (3) Follows up on public reports and findings of cases in the Bukit Soeharto Grand Forest Park area to the Balai Gakkum LHK Kalimantan. Inhibiting factors in law enforcement efforts include (1) Indications of manipulation in judges' decisions, (2) Legal Regulations in Article 39 letters a and b of Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction, (3) Protection from irresponsible individuals, and (4) Lack of legal awareness among the community around the Bukit Soeharto Grand Forest Park area.. Conclusion: The results of the study indicate that in law enforcement efforts against illegal coal mining activities in the Bukit Soeharto Grand Forest Park area, there are factors inhibiting law enforcement originating from the legal regulations themselves which are indications of manipulation in the judge's decision against investors, although they are the masterminds behind the illegal coal mining activities, these investors do not act directly in the field so that there can be indications of manipulation in the judge's decision. In addition, the legal regulations in Article 39 letters a and b of Law Number 18 of 2013 concerning the Prevention and Eradication of Forest Destruction which regulate the investigation period also affect the case resolution process.